2021
DOI: 10.1155/2021/5547120
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Forage Mass and Nutritive Value in Sunn Hemp Leaf and Stem Components

Abstract: Sunn hemp (SH; Crotalaria juncea L.) is a fast-growing, annual, warm-season tropical legume that could complement less productive cool-season forages such as tall fescue during summer. Little is known about seasonal forage mass and nutritive value partitioning in SH plant components when SH is managed for forage. We determined partitioning of forage mass and nutritive value (crude protein (CP), in vitro true digestibility (IVTD), neutral detergent fiber (NDF), acid detergent fiber (ADF), and neutral detergent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…In contrast, SP concentrations in sunn hemp were greatest at the first harvest and declined with successive harvesting. These results are congruent with previous research, as sunn hemp has previously been shown to have CP concentrations >20% (Eberle & Shortnacy, 2021; Lepcha & Naumann, 2021). Sunn hemp's decline in SP was likely related to a decrease in leaf/stem ratio as the plants grew, as reported by Lepcha et al.…”
Section: Forage Mass Sampling Protocols and Nutritive Value Analysessupporting
confidence: 93%
“…In contrast, SP concentrations in sunn hemp were greatest at the first harvest and declined with successive harvesting. These results are congruent with previous research, as sunn hemp has previously been shown to have CP concentrations >20% (Eberle & Shortnacy, 2021; Lepcha & Naumann, 2021). Sunn hemp's decline in SP was likely related to a decrease in leaf/stem ratio as the plants grew, as reported by Lepcha et al.…”
Section: Forage Mass Sampling Protocols and Nutritive Value Analysessupporting
confidence: 93%
“…Studies of the chemical compositions, N fractions, and in vitro digestibility have been recommended to elucidate the nutritive values of forage for ruminant feeding regimes [34,35]. The analyzed CP, NDF, and ADF levels for the GMSH crop were consistent with those for SH plant materials reported by Lepcha et al [36]. The present study was the first report of N fractions determined in GMSH crop.…”
Section: Characteristics Of Gmsh Crop As Ensiling Materials and Poten...supporting
confidence: 83%
“…When applying fertilizers, SH can be cut after 35 days of planning for receiving CP crop [36]. For late cuts, the results show a very high ADL (95 g/kg DM), which probably suppresses fiber utilization in livestock production.…”
Section: Characteristics Of Gmsh Crop As Ensiling Materials and Poten...mentioning
confidence: 99%
“…Additionally, they reported that the proportion of stems in the DMY had increased from around half at 6 weeks to over two-thirds at 9 weeks after planting. Lepcha and Naumann [28] reconfirmed these differences in ADF and NDF between the leaves and stems. They pointed out that the fiber concentration variation because of the cumulative degree days is associated with the proportions of structural tissues, e.g., xylem and sclerenchyma.…”
Section: Discussionmentioning
confidence: 84%
“…The whole plant TN concentration depends on the leaf/stem ratio in some legumes due to the concentrations of TN in leaves and stems differing [26]. Mansoer et al [27] and Lepcha and Naumann [28] also reported differences in sunn hemp TN concentrations between leaves and stems. In addition, Mansoer et al [27] reported a significant TN decrease from 3 to 6 weeks after planting and a slight TN decrease from 6 to 9 weeks after planting in both leaves and stems.…”
Section: Discussionmentioning
confidence: 99%